Digital Transformation of Islamic Education in Pesantren Madura - Mohammad Hasan; Muhammad Taufiq; HÃ¼seyin Elmhemit (State Islamic Institute of Madura, 2023)
Digital transformation is an inevitability in the era of society 5.0. This study examined the digital transformation of Islamic education of Pesantren in Madura. This study employed a qualitative approach, focusing on social education. The study was conducted using interview techniques for Kiai, santri, and researchers in Madura. There were three social facts in the digital transformation of Islamic education. First, the digital transformation in Kiai Pesantren Madura Perspective. Second, implementation of digital transformation of Islamic education at Pesantren Madura. Third, opportunities and challenges for pesantren in facing digital transformation in Islamic education. The Kiai in Pesantren Madura who initially practiced traditional Islamic education were following the development of digital transformation. The positive response can be seen from their perspective on the digital transformation of Islamic education and its implementation in facing digital transformation. Also, some Pesantren have prepared digital literacy facilities and human resources. Even though they have great opportunities in implementing digital transformation, they have the challenge of limited human resources and facilities.